Skilled performance tests and their use in diagnosing handedness and footedness at children of lower school age 8–10 - Musalek, Martin (Frontiers in Psychology, 2015)
Previous research has shown that hand and foot preferences do not develop in parallel in children and it has been discovered that in children foot preference stabilizes later. Therefore, the aim of this study is to verify whether the differences in this stabilization will also be manifested through less consistent results of selected skilled foot performance tests in a comparison with selected skilled hand performance tests. A total of 210 8-10 year old children from elementary schools were recruited for this study. Hand and foot preferences were first tested using hand and foot preference observable measure tasks; consequently, all participants performed four skilled hand performance tests and three foot performance tests. Unlike in complex skilled hand performance tests, which showed a significant convergent validity .56 - .89 with hand preference tasks, in complex skilled foot performance tests a very low convergent validity .25 - .46 with foot preference tasks was detected. The only skilled foot performance indicator which showed an acceptable convergent validity with foot preference tasks was the “foot tapping” test .65 - .85, which represents rather a gross motor activity. Moreover, further results of the tests suggest that complex or fine motor performance tests used for diagnosing laterality of the lower limb that have a manipulative character probably do not represent suitable indicators for children in the given age category. The same trend was revealed in both females and males. This indicates that the level of laterality assessed as difference in skilfulness between the preferred and the non-preferred limb in children in the given age group probably develops in the same way in both genders.